Implementasi Aplikasi Perpustakaan SMAN 1 Koba Dengan Metode Scrum Berbasis Android - Dwi Yuny Sylfania; Fransiskus Panca Juniawan; Iski Zaliman (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2023)
The application of information technology is now implemented in almost all areas of our life. One of them is in the library where information technology applications can play a role in library book loan transactions. This is also applies to SMAN 1 Koba where the process of borrowing and returning books at SMAN 1 Koba still uses the traditional method, namely by recording in the library ledger. There are many drawbacks to using this traditional system, including inefficiency in terms of reporting and transaction services. To overcome this problem, we propose an Android-based library application that can be used to find out the transaction process in the library with catalog features, warehouses, book returns, maintain master data so that it can help manage the book collection in the library, the book search process uses catalogs, and book reports in the form of graphs. This study uses the Scrum method as a software development method. The programming languages used are java and PHP, and use MYSQL for the database. This study uses the black box testing method with functional test results that are all good.